Kajian Deskriptif Supervisi Pendidikan Teknologi Kejuruan pada Laboratorium Dasar dan Pengukuran Jurusan Teknik Elektro - Rima Sartika; Riki Mukhaiyar (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This study aims to describe the existence of PTK supervision which makes a better management system. The informant in this study was the head of the laboratory and education laboratory institution (plp). This research is a qualitative descriptive study. The research was conducted at the basic and measurement laboratory of the electrical engineering department. The method of data collection was carried out using the observation method to determine the conditions and situations of the existing facilities and infrastructure in the laboratory, this interview method was carried out with the head of Labor and PLP related to laboratory management and documentation methods to obtain data in the form of images and supporting documents to support research. In this study, to obtain the validity of the data, triangulation was carried out to adjust the data collected according to the field, by comparing the results of interviews with documentation and documents related to basic and measurement laboratory management. So, it can be said that with PTK supervision, a better management system in the Basic and Measurement laboratory of the electrical engineering department includes planning aspects, organizing aspects, implementation aspects, and supervision aspects.